Homografts versus stentless bioprosthetic valves in the pulmonary position: a multicentre propensity-matched comparison in patients younger than 20 years†. (7th February 2019) - Marathe, Supreet P; Bell, Douglas; Betts, Kim; Sayed, Sajid; Dunne, Benjamin; Ward, Cameron; Whight, Chris; Jalali, Homayoun; Venugopal, Prem; Andrews, David; Alphonso, Nelson
Abstract: OBJECTIVES: The aim of this study was to compare the performance of pulmonary homografts with stentless bioprosthetic valves [Medtronic Freestyle™ (Medtronic, Minneapolis, MN, USA)] in the pulmonary position in patients with congenital heart disease (CHD) younger than 20 years. METHODS: Between January 2000 and December 2017, 215 patients were retrospectively identified from hospital databases in 3 congenital heart centres in Australia. Valve performance was evaluated using standard criteria. Propensity score matching was used to balance the 2 treatment groups. RESULTS: Freedom from reintervention for patients who received a pulmonary homograft ( n  = 163) was 96%, 88% and 81% at 5, 10 and 15 years and for patients who received a Freestyle™ valve ( n  = 52) was 98%, 89% and 31% at 5, 10 and 15 years, respectively. Freedom from structural valve degeneration for patients with a homograft was 92%, 87% and 77% at 5, 10 and 15 years and for patients with a Freestyle valve was 96%, 80% and 14% at 5, 10 and 15 years, respectively. In the first 10 years, there was no difference in outcomes [reintervention hazard ratios (HR) = 0.69, 95% confidence intervals (CI) (0.20–2.42), P  = 0.56; structural valve degeneration HR = 0.92 (0.34–2.51), P  = 0.87]. After 10 years, the recipients of the Freestyle valves were at higher risk of both outcomes [reintervention HR = 7.89; 95% CI (2.79–22.34), P  < 0.001; structural valve degeneration HR = 7.41 (2.77–19.84), P  < 0.001]. The findings were similar when analysed by implantation in the orthotopic position and in the propensity-matched groups. CONCLUSIONS: The Freestyle stentless bioprosthetic valve is a comparable alternative to cryopreserved pulmonary homografts up to 10 years after implantation when implanted in an orthotopic pulmonary position in patients younger than 20 years with CHD.